2018
DOI: 10.1007/s00167-018-5207-9
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric polyethylene inserts promote favorable kinematics and better clinical outcome compared to symmetric inserts in a mobile bearing total knee arthroplasty

Abstract: Your article is protected by copyright and all rights are held exclusively by European Society of Sports Traumatology, Knee Surgery, Arthroscopy (ESSKA). This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
4
26
0
Order By: Relevance
“…The decrease in stress will then bring to better performance of the tibial component, in terms of cement stability and lift-off: the lesser the stress coming from the femoral component, the less stress at the tibial component-bone interface. This outcome is thus in agreement with the findings of the previous study, 15 and it can be a reason for many patients implanted with the AD to feel less pain rather than the ones with the SD.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The decrease in stress will then bring to better performance of the tibial component, in terms of cement stability and lift-off: the lesser the stress coming from the femoral component, the less stress at the tibial component-bone interface. This outcome is thus in agreement with the findings of the previous study, 15 and it can be a reason for many patients implanted with the AD to feel less pain rather than the ones with the SD.…”
Section: Discussionsupporting
confidence: 92%
“…The biomechanical study showed that the ranges for the rotation between tibia and insert are in agreement with the clinical-numerical study previously carried out and published 15,33 ; the AD insert design is furthermore able to internally/externally rotate in agreement with the femur, thus limiting the relative motion between the two. This factor is in agreement with the findings of the previous study [ 15], which stated that the stresses found in case of AD design were lower if compared to the ones in SD: indeed, the higher compliance of the insert with femoral internal-external rotation enables contact areas between the two components to be broader and to maintain this situation along the whole motion, resulting then in the lower stresses.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations